Problems of methods for assessing the professional competence of forensic experts in the production of construction-technical expert examinations - Kuznetsov R. V. (Interactive science, 2022)
The article deals with the issues connected with the level of expert qualification of experts and the mechanism of quality control of expert opinions issued in the sphere of forensic construction-technical expertise. The peculiarities of experts' conclusions examination by courts and the criteria of examination of specialist competence of the expert were determined. The analysis of current legal issues of forensic construction-technical expertise and innovations of normative-legal regulation, as well as a number of problems associated with the qualification of experts, due to the peculiarities of their training and attestation
Keywords: профессиональные компетенции; professional competence; судебная строительно-техническая экспертиза; специальные навыки; заключение экспертизы; сертификация судебных экспертов; судебные эксперты-строители; forensic construction-technical expertise; special skills; expert opinion; certification of forensic experts; forensic construction experts